Spatio-Temporal Analysis of Land Use Change and Its Driving Factors in Layyah, Punjab, Pakistan - Sajid, M.; Mohsin, M.; Mobeen, M.; Rehman, A.; Rafique, A.; Rauf, M.; Ali, G. (The Nucleus, 2023)
Specific objective of this study was to find out the distribution of various land use changes in District Layyah from 2000 to 2020 using geographic information system (GIS) and remote sensing (RS) techniques, and the forces or factors that lead to land use change. District Layyah has experienced remarkable land use and land cover (LULC) changes for the past three decades. Three Landsat satellite images i.e. thematic mapper (TM), Landsat enhanced thematic mapper plus (ETM+) and operational land imager (OLI)/ TIRS for the years 2000, 2010 and 2020 were acquired from USGS website in order to detect the land use changes. By using ERDAS Imagine software, the maximum likelihood classification was employed in order to classify the images. The spatial and spectral distribution of five land use types was made including i.e. Water, Built-up, Vegetation, Desert, Bare and Sparse land. Ground Truth points were noted and these points were used for the validation and classification of the images. This accuracy showed an overall accuracy rate of 85% with a Kappa coefficient of 0.9 which demonstrated the basic classification method because the images used in the research were highly good. Results showed that the rise was revealed in Vegetation, Built-up and Water land uses from the year 2000 to 2020. On the other side, the decrease in Bare and Sparse land and Desert land use was calculated. The main driving factors behind these LULC changes were found the growth in population, agro-technological advancement and various physical factors (e.g. availability of water and so on), resulting an increase in built-up area. Present research will be beneficial in understanding the most important land use changes to estimate the future change trends in various land use classes for policy making and land use management.